(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The essay shows the level of (in)implementation of the principle of equity in access to services offered by the National Health Service (NHS), examining access to services by migrants and people living in conditions of economic and social marginality. To this end, the Author first illustrates the legal requirements necessary for access to health care, then describes the factors that prevent or hinder the use of services. Finally highlights the remedies provided by case law and some recent initiatives put in place by political institutions. The analysis will be an opportunity to consider how, within a general critical framework, a new model of administrative action can be discerned that deserves to be enhanced, even beyond the health sector.